Effect of a new Lactobacillus plantarum product, LRCC5310, on clinical symptoms and virus reduction in children with rotaviral enteritis. Issue 38 (18th September 2020) - Shin, Do Young; Yi, Dae Yong; Jo, Soojin; Lee, Yoo Min; Kim, Jong-Hwa; Kim, Wonyong; Park, Mi ri; Yoon, Seok min; Kim, Yunsik; Yang, Siyoung; Lim, In Seok
Abstract: Background: Rotavirus is one of the most common causes of infantile enteritis. In common enterocolitis, probiotic organisms, including Lactobacilli, are effective in treating diarrhea. A new species, Lactobacillus plantarum (LRCC5310), which was shown to inhibit the adherence and proliferation of rotavirus in the small intestine through animal experiments, was investigated for the efficacy and safety of patients with rotaviral enteritis. Methods: LRCC5310 (Group I) and control (Group II) groups consisting of children who were hospitalized for rotaviral enteritis were compared, and the medical records of patients (Group III) who were hospitalized for rotaviral enteritis during the same study period were retrospectively analyzed. Clinical symptoms were compared and stool samples were collected to compare changes in virus multiplication between Groups I and II. Results: Groups I, II, and III comprised 15, 8, and 27 children, respectively. There were no differences in clinical information among the groups at admission. In Group I, a statistically significant improvement was noted in the number of patients with diarrhea, number of defecation events on Day 3, and total diarrhea period as opposed to Group II ( P = .033, P = .003, and P = .012, respectively). The improvement of Vesikari score in Group I was greater than that in the other groups ( P = .076, P = .061, and P = .036, respectively). Among rotavirus genotypes, 9 (22.5%) strains and 8 (20.0%) strains belonged to the G9P8 and G1P8 genotypes, respectively. The virus reduction effect, as confirmed via stool specimens, was also greater in Group I. No significant side effects were noted in infants. Conclusion: LRCC5310 improved clinical symptoms, including diarrhea and Vesikari score, and inhibited viral proliferation in rotaviral gastroenteritis.